If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 49(y + 3) + y = 5y + 12 Reorder the terms: 49(3 + y) + y = 5y + 12 (3 * 49 + y * 49) + y = 5y + 12 (147 + 49y) + y = 5y + 12 Combine like terms: 49y + y = 50y 147 + 50y = 5y + 12 Reorder the terms: 147 + 50y = 12 + 5y Solving 147 + 50y = 12 + 5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-5y' to each side of the equation. 147 + 50y + -5y = 12 + 5y + -5y Combine like terms: 50y + -5y = 45y 147 + 45y = 12 + 5y + -5y Combine like terms: 5y + -5y = 0 147 + 45y = 12 + 0 147 + 45y = 12 Add '-147' to each side of the equation. 147 + -147 + 45y = 12 + -147 Combine like terms: 147 + -147 = 0 0 + 45y = 12 + -147 45y = 12 + -147 Combine like terms: 12 + -147 = -135 45y = -135 Divide each side by '45'. y = -3 Simplifying y = -3
| 5x-9=(x-2) | | 7x+8y-16=0 | | 3.00=55b | | 20t+40= | | 120=5(3+x)+2x | | 4a-14= | | C=4x-2y | | 2(4-7)=7u+2-2(-5u-1) | | -12-12(8+5n)=8n+28 | | -16t^2+48t+36=0 | | 13.5-0.3k+2.5-0.8k=7-1.1k-8.4 | | 2x+8-6(x+1)=3x+7 | | 2(6d-3)=6(5+3D) | | y-0=-3(x-2) | | 2[4-(-4x-4)]=64x+72 | | 2a-5(a-2)+4(b-2)= | | a=1/2h(b1b2) | | 2[4-(4x-4)]=64x+72 | | (w-3)(w+1)= | | 2-3(x+4)=9-(3x-2) | | =x^2-2x-11 | | R+0.5=0.7 | | 4+8=6+2t | | 4(u+5)=-8u-40 | | -2(17x-4)+7(5x-7)-3=9-2 | | 7x+18=42x+11 | | -4(3x+5)=2(6-2x) | | -4x-4(1-2x)=7+4x | | 16x+5=10y | | (Q*0.33)+Q=72 | | 2(5y-7)+10=36 | | 4x+8-6x=7+6x-7 |